A qualitative evaluation of the impact of a Good Life Club on people living with dementia and care partners. (October 2021) - Morris, Lydia; Innes, Anthea; Smith, Sarah; Wilson, Jack; Bushell, Sophie; Wyatt, Megan
Background: Research suggests there is a lack of post-diagnostic support to enable people living with dementia to fulfil social and active lives throughout their dementia journey. Gardening has been found to have many benefits for people living with dementia. Although such research is important, most research frames people with dementia as passive recipients of stimulation. Research into the impact of a community-based gardening group, where people living with dementia are active in the development of an outdoor space, is underdeveloped. Knowledge about the impact of participating in such groups is also sparse. The Good Life Club (GLC) was co-developed and evaluated to respond to these gaps. Objectives: The primary aim of this article is to present the findings regarding the impact of attending the GLC on the self-reported well-being for people living with dementia and care partners. Methods: Qualitative data were collected via 22 semi-structured interviews. Fourteen interviews were conducted before the GLC and eight after the GLC. Thematic analysis was used to analyse data. Dementia Care Mapping data were collected to supplement the interview data. Findings: Four key themes were identified. The first was that participants considered having active participation in social life to be a key aspect of living a good life. The second was that the way that the GLC was set up and delivered gave the participants ownership of the GLC and within this they felt able to contribute. The third was the importance of social connectedness and peer support to the well-being of both people living with dementia and care partners. Fourth, positive mood and well-being was directly experienced through gardening. Conclusions: The combination of long-term investment of time and energy to the GLC, ongoing friendships and in-session autonomy act as key ingredients in creating a group that is relaxed, full of humour and highly valued.